Types Of Responsibility In Preventing Illegal Circulation Of Cultural Assets - Ergashev Jahongir Sheraliyevich (Genius Publishing Group, 2025)
The article discusses the concept, types, content, and essence of responsibility for the illegal transportation of cultural resources across the customs border and some problematic issues that arise in determining the responsibility for preventing the unlawful circulation of cultural resources.
Keywords: Customs authorities; customs crimes; types of criminal responsibility